Characterization of lignocellulosic biomasses and their thermal processing: Status and opportunities at the Instituto Tecnológico de Costa Rica - Puente-Urbina, Allen (2022)
Lignocellulosic biomasses are feedstocks with low carbon footprints, useful for the production of energy, materials and chemicals, which can come from different sources, including agro-industrial activities and fast-growing plantations. In Costa Rica, despite the fact that part of the usable biomasses is already in use, there is still potential. Some of the ways in which they can be used and provide a wide range of products is through thermal processing via combustion to obtain energy, torrefaction or carbonization to obtain solid fuels, pyrolysis to obtain (predominantly) liquid products or gasification to obtain gases that can be used as fuels or further processed to obtain high-value chemicals. To achieve a practical implementation of these processes, it is necessary to adequately characterize the starting materials, as well as to know in detail their behavior under specific processing conditions. For both, the Instituto Tecnológico de Costa Rica (ITCR) has adequate instrumental capacity and expertise. Available tools such as physicochemical characterization methods using traditional chemical analyses, instrumental analyses (using spectroscopic, microscopic, diffractometric and thermal methods, among others) as well as capabilities in torrefaction, carbonization, pyrolysis, gasification and computational simulations, together with well-trained staff with different backgrounds, make this institution a suitable place to study and promote technologies that may be of general interest. In this work, successful experiences and opportunities at the ITCR related to the characterization of lignocellulosic biomasses and their thermal processing are analyzed.